Host plants, herbivores and natural enemies in Kenyan horticulture : tritrophic interactions involving Liriomyza leafminers (Diptera : Agromyzidae) - Kruger, Kerstin (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2010.